Implementasi Smart Village dalam Mewujudkan Desa Digital di Desa Cijantra Kecamatan Pagedangan Kabupaten Tangerang - Khaerunisa, Siti; Syamsudin, Udin; Rantau, Muhammad Ibrahim (Innovative: Journal Of Social Science Research, 2024)
Cijantra Village, located in Pagedangan District, Tangerang Regency, is an example of a village that is undergoing a transformation towards a digital village. This research aims to find out how Smart Village is implemented in creating a digital village and what are the supporting and inhibiting factors for the village government and the community of Cijantra village, Pagedangan subdistrict. The object of this research is the implementation of Smart Village in creating a digital village in the community of Cijantra Village, Pagedangan District, Tangerang Regency. The research method used is qualitative with descriptive research type. The data collection stage in this research consists of observation, interviews and documentation. Qualitative data analysis techniques, namely, data collection, data reduction, data presentation and drawing conclusions. The research results found that there had been a change in the public service system in Cijantra village through the use of the Simpeldesa application by paying attention to 4 indicators, namely resources, institutions, technology and sustainability. However, there are still obstacles found in realizing this digital village, namely people who still do not understand the use of technology and there is still a digital gap in the use of these applications due to the lack of socialization for the community in Cijantra Village, Pagedangan District in Tangerang Regency, which has experienced a development.